Moral status of participants in war : a scale to measure degrees of moral innocence - Quek, Patrina, Jing Ying (2019)
Just War Theory has been a prominent theory in war literature. It aims to establish a framework of morally permissible causes to wage a war, as well as actions that are morally permitted in a war. However, it gives an oversimplified distinction between the moral status of combatants and civilians. As such, this paper will propose a scale to measure the degrees of moral innocence for participants who are directly and indirectly involved in a war. I will apply this scale to a realistic case and stress that it is absolutely impermissible to cause harm (both intended and highly foreseeable harm) to the morally innocent. I will also consider conditions which would make a tactical bombing permissible. This paper wants to leave readers with the idea that the distinction in moral status of combatants and civilians is not as simple as what is stated in Just War Theory. We have to consider different degrees of moral innocence on a scale. While we may not always be able to ascertain where one stands on this scale because of one’s multiple roles and conflicting identities, we should always try to minimize harm imposed on the morally innocent.